Integrative preventive medicine - Carmona, Richard H.; Liponis, Mark, 1958- ([New York] : Oxford University Press, 2017)
For most clinicians, the science and evidence for many integrative therapies is largely unknown or considered suspect. Most physicians don't have time to learn integrative approaches and aren't sure what to recommend or which approaches have merit or improved outcomes. Here, clinicians have easy access to the best practices in integrative medicine and expectations for outcomes.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 20, 2017).
Keywords: Integrative medicine; Medicine, Preventive